Advanced synthesis of meta-antenna radiation pattern enabled by transformation optics. (27th March 2019) - Sedeh, Hooman Barati; Fakheri, Mohamad Hosein; Abdolali, Ali
Abstract: Multi emission meta-radiating structures have been an important area of focus due to their potential applications in multi-user scenarios. Thereby, based on the concept of multi-folded transformation optics, a general approach for enabling the customizable multiple beam radiation of a planar antenna is propounded. The presented method is competent not only in creating any desired number of beams but also in adjusting their directivities. Antithetical to phased array antennas, with their complex feeding, heavyweight and costly elements, this goal was achieved via utilizing simple homogeneous materials elaborately designed by multiple folding of the virtual spaces to physical ones with an affine transformation. Several illustrative numerical simulations were performed in order to highlight the capability of the presented method in manipulating the planar source radiation. A meta-antenna structure consisting of a multi-folded layer and the patch antenna underneath, was designed, fabricated, and measured to authenticate the concept. The structure divides the radiated wave into two beams with arbitrary directions and different directivities. The experimental results of the realized meta-antenna structure exhibited good agreement with numerical simulations and theoretical predictions. The proposed approach could find applications in several fields of engineering where multiple emission is of utmost importance such as multi-input–multi-output systems, or could be used in waveguide applications like power dividers.